Trauma, Mental Health Distress, and Infectious Disease Prevention Among Women Recently Released From Incarceration - Johnson, Karen A.; Hunt, Timothy; Puglisi, Lisa B.; Maeng, Daniel; Epa-Llop, Amali; Elumn, Johanna E.; Nguyen, Antoinette; Leung, Ashley; Chen, Rachel; Shah, Zainab; Wang, Jiayi; Johnson, Rachel; et al. (Frontiers in Psychiatry, 2022)
Background U.S. women recently released from incarceration experience significantly higher rates of trauma and exacerbation of mental health conditions, and the period following release has been identified as a window of heightened risk for mental health distress and human immunodeficiency virus (HIV), sexually transmitted infections (STI) and hepatitis C (HCV) transmissions. Despite these vulnerabilities, and an urgent need for supports, optimal engagement strategies remain unclear. WORTH Transitions is a program made up of two evidence-based interventions focused on improving the health of women returning to the community from incarceration with substance use disorders. Combining the two was designed to reduce HIV/STIs/HCV risks and increase overall health treatment engagement using a community health worker led intervention. Methods We examined associations between trauma, mental health symptomology, and HIV/STI/HCV outcomes among women who engaged in the WORTH Transitions intervention (N = 206) Specifically, bivariate and longitudinal multivariate models were created to examine associations between trauma and mental health distress (defined as depressive and PTSD symptoms), on (1) types of engagement in HIV/STIs/HCV prevention and behavioral health services; and (2) HIV/STIs/HCV risk outcomes. The women who engaged in the intervention were 18 years and older and some were White, Black and other racial or ethnic minority. Results PTSD symptomology and being a Black or indigenous woman of color was significantly (p = 0.014) associated with individual or group session engagement. Neither trauma nor PTSD symptoms were associated with higher HIV/STIs/HCV risks. Instead, relative to those who did not engage in HIV/STI/HCV risky behaviors, PTSD symptomology (p = 0.040) was associated with more than 3-fold increase in the probability of being lost to follow up (relative risk ratio = 3.722). Conclusion Given the impact of PTSD-related symptoms on driving both engagement in HIV/STIs/HCV prevention services and intervention attrition among women leaving incarceration, physical and behavioral health interventions must be both overtly trauma- and mental health-informed. As was the case with WORTH Transitions, physical and behavioral health services for this population must include intentional and active support of the forms of treatment participants endorse to ensure maximal engagement.